2023
DOI: 10.1002/ece3.10545
|View full text |Cite
|
Sign up to set email alerts
|

The High–Low Arctic boundary: How is it determined and where is it located?

Ksenia A. Ermokhina,
Anna I. Terskaia,
Tatiana Yu. Ivleva
et al.

Abstract: Geobotanical subdivision of landcover is a baseline for many studies. The High–Low Arctic boundary is considered to be of fundamental natural importance. The wide application of different delimitation schemes in various ecological studies and climatic scenarios raises the following questions: (i) What are the common criteria to define the High and Low Arctic? (ii) Could human impact significantly change the distribution of the delimitation criteria? (iii) Is the widely accepted temperature criterion still rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…This supports the generally held assumption that lake drainage introduces landcover heterogeneity into the landscape (Bartsch et al, 2023b). Raynolds et al (2019) A1), this is supported by recently studies, for example showed Ermokhina et al (2023) that the July isotherms of 6 °C are changing northwards. This may have an impact on zone specific results and updated boundaries should be considered for future studies.…”
supporting
confidence: 84%
“…This supports the generally held assumption that lake drainage introduces landcover heterogeneity into the landscape (Bartsch et al, 2023b). Raynolds et al (2019) A1), this is supported by recently studies, for example showed Ermokhina et al (2023) that the July isotherms of 6 °C are changing northwards. This may have an impact on zone specific results and updated boundaries should be considered for future studies.…”
supporting
confidence: 84%
“…We found no conclusive evidence that distance to infrastructure affects species richness in Western Siberia. Despite strong evidence of impact of anthropogenic activities on the vegetation of the region (Ektova & Morozova, 2015;Ermokhina et al, 2023;Forbes, 2013;Golovatin et al, 2010;Golovnev et al, 2016;Veselkin et al, 2021), a sensitivity analysis suggests that most of the impact of the distance to infrastructure predictor is attributable to other predictors (Figure S2). At the same time, indirect indicators such as relatively high explained deviance of the distance (11%) show that there might be a potential relationship that cannot be confidently detected with the data available.…”
Section: Discussionmentioning
confidence: 98%
“…We found no conclusive evidence that distance to infrastructure affects species richness in Western Siberia. Despite strong evidence of impact of anthropogenic activities on the vegetation of the region (Ektova & Morozova, 2015 ; Ermokhina et al., 2023 ; Forbes, 2013 ; Golovatin et al., 2010 ; Golovnev et al., 2016 ; Veselkin et al., 2021 ), a sensitivity analysis suggests that most of the impact of the distance to infrastructure predictor is attributable to other predictors (Figure S2 ). At the same time, indirect indicators such as relatively high explained deviance of the distance (11%) show that there might be a potential relationship that cannot be confidently detected with the data available.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate community-level species richness, we used geobotanical data from the Russian Arctic Vegetation Archive (Ermokhina et al, 2022;Zemlianskii et al, 2023). These data consist of 1483 Braun-Blanquet plots established in homogenous vegetation collected during the 2005-2017 field campaigns in the Western Siberian tundra (Figure 1) (Zemlianskii et al, 2023).…”
Section: Geobotanical Plotsmentioning
confidence: 99%